(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study ascertained the extent of utilization of e-learning resources by business education students in public tertiary institutions in Enugu State. Two research questions were posed and four hypotheses tested. A total of 1407 business education students in four public tertiary institutions in Enugu State made up the population of the study, out of which 312 students were used as sample. The research instrument was a structured questionnaire titled “The Extent of Utilization of E-learning Resources by Business Education Students” (EUERBES). Three experts validated the instrument and a reliability test using Cronbach alpha method yielded correlations of 0.87 and 0.76 B1-B2 of the instrument respectively. Mean rating was used to answer the research questions while z-test was used to test the hypotheses at 0.05 level of significance. The findings of the study revealed among others that business education students in public tertiary institutions utilized e-learning resources for peer tutoring to a high extent and they moderately utilize e-learning resources for class discussions. To encourage the utilization of e-learning by business education students, it was recommended, among others, that the management of public tertiary institutions in Enugu State should provide e-learning resources like digital libraries and free wireless internet connections on the campuses.